Pinjaman Online di Masa Pandemi Covid-19 bagi Masyarakat Aceh - Asmah Savitri; Angga Syahputra; Husna Hayati; Heny Rofizar (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Online loans are digital financial service innovations that are very touching to people in need, especially during the Covid-19 pandemic. September 2020 data shows online loans have disbursed Rp. 417.6 billion to the people of Aceh. So that research on the impact of pinjol during the pandemic for the people of Aceh is important. This study uses a qualitative research type by using a literature study type of research. The results of this study indicate that online loans have a good impact in helping the difficulty of funds for the people of Aceh. However, this study also found that online loans have negative impacts that must be watched out for, including: the rise of illegal online loans, high interest rates and acts of terror and defamation that stalk users of this service